ANTECEDENTS OF E-REFERRALS: A STUDY ON MOBILE BANKING APPLICATIONS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study contributes to the subsisting  literature on Word-of-Mouth by identifying  the demographic and behavioural factors that  motivate people towards making e-referrals  of mobile banking applications. Also the  influence of incentives and incentive amount  is measured. The data for the study is collected  from 120 respondents. The results suggest that  education, age, satisfaction, trust, involvement,  existing word-of-mouth, usefulness, credibility,  incentive and incentive amount positively  influence a customer’s choice of referring  people electronically.
Keywords: E-referrals; mobile banking applications; demographic factors; behavioural factors; incentives